Morphometry of Acetabulum in Adult Bangladeshi Populationon radiographs (Sir Salimullah Medical College Journal, 2025)
Background: Morphometry of acetabulum has important clinical implications as it is crucial to the orthopaedic surgeons for surgical planning before acetabulumsurgery andacetabular cupplacement during total hip arthroplasty andhelp the cliniciansto assess hip dysplasia and hip osteoarthritis. It is also useful to theprosthetistsfor designing better prosthesis of hip joint. Gender differences in the morphometric parameters of acetabulum assist the forensic experts in determination of sex. The present study was designed to evaluatecenter edge angle, acetabular angle of Sharp and Tonnis Angle in adult Bangladeshi population, determine gender differencesand compare findings of the present study with the studieson other Methods: This was a cross sectional analytical study conducted on the Department of Anatomy, Sir Salimullah Medical College, Dhaka from July 2020 to June 2021.Standardized plain anteroposterior pelvic radiographs of seventy adult Bangladeshi population age ranging from 25- 45 years were collected to measure center edge angle, acetabular angle of Sharp and Tonnis angle unilaterally on the radiographs with MB ruler software. Comparisons between male and female parameters were done with unpaired t-test. Statistical analyses were performed using SPSS  24 software .Results: In the present study, the total mean center edge angle was 34.29°±5.66°,the mean center edge angleof male and female were33.95°±5.64° and 35.03°±5.53° respectively. The mean acetabular angle of Sharp was 39.33°±3.29°.The mean valueof male and femalewere 39.53°±3.82° and 39.39°±3.21°respectively. The mean Tonnis angle was 6.74°±4.26°. In male itwas 6.85°±4.05°, while in femaleitwas 6.62°±4.51°. The present study showed no statistically significant gender differencein mean center edge angle, acetabular angle of Sharp and Tonnis anglein adult Bangladeshi population. Conclusion: In the present study center edge angle, acetabular angle of Sharp and Tonnis angle showed no significant gender difference in adult Bangladeshi population.Sir Salimullah Med Coll J 2024; 32: 23-28